STUDY OF COMPOUNDS FROM EXTRACT OF Melochia umbellata (Houtt.) Stapf var. Degrabrata K. (PALIASA) LEAVES THAT HAS POTENTIAL AS ANTIBACTERIAL - Selfi Wullur; Firdaus Firdaus; Hasnah Natsir; Nunuk Hariani Soekamto (Hasanuddin University, 2015)
Determination of antibacterial activity of each extract of M. umbellata (Houtt.) Stapf var. K. degrabrata leaves has been conducted against three strains bacteria Escherichia coli, Staphylococcus aureus, and Shigella dysenteriae by using amoxicillin as a positive control and DMSO as a negative control. Agar diffusion method has been used with MHA medium (Muller Hinton Agar) on variation concentrations of each extract were 2500 ppm, 5000 ppm, 10,000 ppm, and 20,000 ppm N-hexane extract was the most active extract against S. aureus with zone of inhibitions were 10.50 mm, 10.80 mm, 11.00 mm and 11.45 mm, respectively. The most active extract against S. dysenteriae was ethyl acetate extracts with zone of inhibitions were 9.36 mm, 11.55 mm, 11.58 mm and 17.70 mm, respectively. Isolated compound from n-hexane extract was first compound as white powder with a melting point of 75-77 °C which was identified as 1-Tetracosanol and second compound was obtained in the form of a yellow paste which was identified as steroid compound that had long conjugated substituent. These compounds were elucidated based on the data of IR, UV-Vis, 1H-NMR, and 13C-NMR.